Fabrication of hybrid network materials using polyethyleneimine and glycidyl-POSS for CO2 adsorption. (12th June 2020) - Lee, Seung-Hun; Lee, Jae-Ik; Kim, Ki-Young; Lim, Jung-Hyurk; Kim, Kyung-Min
Abstract: PEI-based network materials with polyhedral oligomeric silsesquioxane (POSS) particles as a cross-linker were prepared by the chemical amine/epoxide reaction of PEI and glycidyl-POSS. Glycidyl-POSS is a hybrid molecule with an inorganic silsesquioxane at the core and organic glycidyl groups attached at the corners of the cage. POSS molecules were homogeneously dispersed as the crosslinking point in PEI matrix. These hybrid network materials were fabricated with not only different weight ratio of POSS to PEI but also 1, 4-butanediol diglycidyl ether (BDE) as a cross-linker instead of POSS to confirm the effect of POSS on the CO2 capture performance and thermal stability.